(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
One of the important issues in the psychology of management is the analysis of levels of managerial decision-making and the study of factors influencing it. In the management process, there are four levels of decision-making, within each of which certain skills are required to work. The first level of decision making is the ordinary, everyday level. In this case, the instructions and rules are strictly followed, the situation is assessed properly and control is established. The emerging problem is compared with a set of existing solutions, from which the best option is adopted and implemented. Usually this is done according to the principle "In such situations, you need to do this." Difficulties in such situations may arise due to the incompetence of the decision maker, ignorance of existing guidelines, incorrect assessment of the situation or lack of courage. At this level of decision-making, a creative approach is not required because the decisions of the situation are already predetermined.